2014
DOI: 10.1139/cjfas-2013-0618
|View full text |Cite
|
Sign up to set email alerts
|

Effects of domestication on parr maturity, growth, and vulnerability to predation in Atlantic salmon

Abstract: Domestication can change fitness-related traits. We investigated domestication-induced changes in fitness-related traits in Atlantic salmon (Salmo salar) under naturally enriched laboratory conditions with and without threat of predation. Selection in two strains for rapid growth for three and five generations resulted in two and three times larger sizes of underyearling parr relative to their wild ancestor. An initially larger size and ability to outgrow prey size more rapidly resulted in lower size-selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 73 publications
3
34
1
Order By: Relevance
“…In fact, we showed that maturation‐ and reproduction‐related genes were up‐regulated among the random‐harvested fish (from F 5 to F 11 ), and we have shown earlier that the random‐harvested fish have a higher age‐specific maturation probability than large‐harvested fish (Uusi‐Heikkilä et al., ). This is in agreement with other studies showing that fish held in captivity tend to mature later than their wild conspecifics (Debes & Hutchings, ). Thus, it is possible that in captivity, traits under selection are related to body condition (body fat content), growth, and potentially maturation.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, we showed that maturation‐ and reproduction‐related genes were up‐regulated among the random‐harvested fish (from F 5 to F 11 ), and we have shown earlier that the random‐harvested fish have a higher age‐specific maturation probability than large‐harvested fish (Uusi‐Heikkilä et al., ). This is in agreement with other studies showing that fish held in captivity tend to mature later than their wild conspecifics (Debes & Hutchings, ). Thus, it is possible that in captivity, traits under selection are related to body condition (body fat content), growth, and potentially maturation.…”
Section: Discussionsupporting
confidence: 93%
“…One way to circumvent this challenge is to use a farmed strain that is known to be based on a single or low number of wild populations, either from the onset of domestication (Debes & Hutchings, ; Solberg et al., ), or by altered strain contributions through the first generations of domestication (Einum & Fleming, ). An alternative is to include multiple farmed strains and/or wild populations to identify evidence of parallel evolution.…”
Section: Geneticsmentioning
confidence: 99%
“…Indeed, triploid escapees, which are sterile, may enter freshwater albeit at a considerably reduced frequency compared to diploid escapees (Glover et al., , ). In addition, not all male juveniles escaping to freshwater will become sexually mature as parr, especially because the tendency for parr maturation in farmed strains is lower than in wild populations (Debes & Hutchings, ; Einum & Fleming, ; Morris, Fraser, Eddington, & Hutchings, ; Yates, Debes, Fraser, & Hutchings, ). Therefore, not all escapees found in rivers will reproduce and hybridize with native fish.…”
Section: Ecology Preceding Introgressionmentioning
confidence: 99%
“…The hatchery environment is typically characterised by high densities, a lack of predation and continuous feed availability. Farmed S. salar have exhibited changes in behavioural traits such as increased aggression, higher stress resistance and decreased predator awareness that are attributed to inadvertent selection resulting from the artificial hatchery environment (Einum & Fleming, ; Fleming & Einum, ; Houde et al , 2010 a , b ; Solberg et al , 2013 a ; Debes & Hutchings, ). Thus, direct and indirect selection has resulted in domesticated fish that are adapted to their captive environment and that typically display traits which may be maladaptive in the wild relative to their wild counterparts.…”
Section: Introductionmentioning
confidence: 99%